A glass fiber ceramic silicone sheet and its preparation process

By cross-linking modification of silicone rubber and glass fiber surface modification, ceramic bodies are formed to improve the mechanical properties and interface compatibility of silicone rubber, solving the problem of low strength of silicone rubber at high temperatures, and realizing the Flame retardant and heat insulation.

CN118599320BActive Publication Date: 2024-12-24SUNWAY PRECISION TECHNOLOGY (GUANGDONG) CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410579651.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2024-12-24
Estimated Expiration
2044-05-11

AI Technical Summary

Technical Problem

The structure of existing silicone rubbers such as SiO2 produced by thermal decomposition at high temperatures is loose, unable to effectively protect the inner layer material, and its strength is extremely low and cannot be used in practice. It is necessary to enhance the silicone rubber matrix to improve mechanical properties.

Method used

By cross-linking modification of methylphenyl vinyl silicone rubber, cross-linking agent and glass fiber are introduced as fillers, and surface modification treatment is used to improve the cross-linking degree and interface compatibility, forming a hard ceramic body to resist Burn and insulate.

Benefits of technology

Under high temperature or open flame, the material changes from a flexible rubber state to a hard ceramic body, with good strength and self-support, can effectively isolate flames and temperatures, and is suitable for areas where high temperature stability is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004833498750000071
    Figure BDA0004833498750000071
  • Figure BDA0004833498750000081
    Figure BDA0004833498750000081
  • Figure BDA0004833498750000082
    Figure BDA0004833498750000082
Patent Text Reader

Abstract

The present invention relates to the technical field of compositions of polymer compounds, and specifically discloses a glass fiber ceramic silicone sheet and a preparation process thereof. The glass fiber ceramic silicone sheet comprises the following components in parts by weight: 80 to 150 parts of a silicone rubber matrix, 1 to 2 parts of a cross-linking agent, 20 to 50 parts of fumed silica, 10 to 25 parts of a modified filler, 5 to 10 parts of hydroxy silicone oil, and 1 to 5 parts of a vulcanizing agent. The present invention also provides a preparation process thereof. Compared with the prior art, the glass fiber ceramic silicone sheet prepared by the present invention has improved mechanical stability, and can effectively improve its reliability in practical applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer compound compositions, and in particular to a glass fiber ceramicized silicone sheet and a preparation process thereof. Background Art

[0002] Ceramic polymer composites have been proposed in recent years as a new type of flame retardant, ablation-resistant and thermal insulation material with good mechanical and physical properties, providing new ideas and methods for the field of thermal insulation and refractory materials: they have the excellent properties of ordinary polymer materials such as designability, electrical insulation, and corrosion resistance when used at room temperature. At high temperatures, the polymer matrix and internal fillers undergo physical and chemical reactions to ultimately achieve the effect of transforming from an organic phase to an inorganic ceramic phase, especially forming a smooth and dense ceramic structure on the surface of the material. This special structure can prevent the spread of flames, resist internal oxidation by hot air flow, and have a certain degree of self-support. Therefore, in recent years, research on thermal insulation materials has gradually shifted to ceramic polymer-based composites.

[0003] Ceramic silicone rubber is a relatively new fireproof and high temperature resistant material. It uses organic silicone rubber as the matrix. It is similar to ordinary rubber materials at room temperature and has good mechanical properties. When in a high temperature environment, the material changes from a flexible rubber state to a hard ceramic body, which plays a good protective role and has broad application prospects. Ceramic silicone rubber materials can be widely used not only in the field of fireproof cables, but also in other fields that require fireproof and high temperature resistance. When used in batteries, a dense ceramic layer can be formed under fire or high temperature to protect the normal operation of the internal circuit. At the same time, the ceramic layer itself has a certain strength and plays a compressive role.

[0004] Chinese patent 201910537085.X discloses a high-temperature resistant ceramic silicone rubber and its preparation method and application. The invention mixes high-strength rubber compound, inorganic powder filler and vulcanizing agent to prepare a ceramic silicone rubber composition, and then the ceramic silicone rubber composition and glass cloth treated with silicone acrylic emulsion are compounded by calendering process, and then baked and vulcanized at 115-125°C to obtain a high-temperature resistant ceramic silicone rubber with high strength and good flexibility. It can directly replace mica tape for fire-resistant cable manufacturing, and no dust pollution will be generated during the wrapping process; the cable wrapped with it is ablated in a flame of 650-950°C for 3 hours, and the line can still work normally, and a ceramic-like high-hardness shell is formed after ablation. The shell has good electrical properties and mechanical strength, and the line can still work normally under high-intensity vibration and water spray. It has higher flame retardancy and can be used for the manufacture of advanced fire-resistant cables.

[0005] Chinese patent 201510073286.0 discloses a method for preparing a ceramic fireproof and fire-resistant silicone rubber, wherein the raw materials for preparing the ceramic fireproof and fire-resistant silicone rubber include organic silicon rubber compound and ceramic powder, and the organic silicon rubber compound is prepared from raw materials including silicone rubber, fumed silica, structural control agent and ceramic improver, and then mixed with ceramic powder to obtain ceramic fireproof and fire-resistant silicone rubber. The ceramic fireproof and fire-resistant silicone rubber prepared by the invention has improved mechanical stability, avoids the silicone rubber layer from being severely degraded in a low temperature environment, resulting in cracking or reduced density of the final ceramic shell layer, and effectively improves the reliability of fire-resistant cables using the silicone rubber as the fire-resistant layer material in practical applications.

[0006] Due to the large amount of SiO2 and other substances produced by the thermal decomposition of silicone rubber at high temperatures, although it has good electrical insulation and flame retardant effects, it has a loose structure and appears as a powder with no strength. It is very easy to detach from the surface of the material under the continuous erosion of high-temperature hot air flow and cannot effectively protect the inner layer material. Therefore, the silicone rubber matrix must be strengthened to improve the mechanical properties of silicone rubber. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to provide a glass fiber ceramic silicone sheet and a preparation process thereof.

[0008] Without reinforcing fillers, the strength of silicone rubber is extremely low, and the tensile strength is often lower than 1MPa, which cannot be used in practice. Therefore, the silicone rubber matrix must be reinforced to improve the mechanical properties of silicone rubber. The reinforcement of the silicone rubber matrix is ​​often to introduce a crosslinking agent, a reinforcing filler, or a combination of the two, so as to improve the mechanical properties and other properties of the silicone rubber. The present invention crosslinks and modifies methylphenyl vinyl silicone rubber, and chemically reacts the crosslinking agent with the silicone rubber matrix to improve the degree of crosslinking. The multiple groups contained in the crosslinking agent can crosslink with the silicone rubber matrix to varying degrees, thereby improving the mechanical properties of the material.

[0009] Introducing fiber as filler can also improve the strength of the material, but filler and silicone rubber belong to inorganic and organic phases respectively. Through surface modification and other methods, the interfacial effect of the composite material can be effectively improved and the compatibility of the two phases can be improved. At present, surface modification mostly adopts means such as surface organic modification, physical coating and mechanical force modification, and the effect of organic modification on the surface of powder is often better. Through the reaction between inorganic powder and modifier and coating a layer of organic group on the surface, the agglomeration between powders is reduced and the interaction with the organic matrix is ​​enhanced. The present invention chemically modifies the glass fiber. The surface energy of the modified glass fiber is reduced due to the presence of multiple hydrophilic groups, thereby improving the interfacial effect with the silicone rubber group, thereby making the compatibility better. In addition, the unsaturated double bonds in the modifier can also be cross-linked with the silicone rubber matrix and the cross-linking agent, thereby further strengthening the degree of cross-linking, making the combination tighter, thereby achieving a further improvement in mechanical strength. The present invention obtains the glass fiber ceramic silicone sheet by die-cutting after mixing the components, performing primary vulcanization and secondary vulcanization. The material is transformed from a flexible rubber state to a hard ceramic body under high temperature or open flame. On the one hand, it can play a role in blocking and isolating flames and temperature, isolating the protected material from the outside world. On the other hand, the heat insulation sheet has good strength and self-supporting properties, can withstand certain external impacts, and protects the material from being destroyed by external forces as much as possible. Therefore, it is suitable for use in fields such as batteries that require high temperature stability.

[0010] To achieve the above-mentioned purpose, the present invention provides a glass fiber ceramic silicone sheet, comprising the following components in parts by weight: 80 to 150 parts of a silicone rubber matrix, 1 to 2 parts of a cross-linking agent, 20 to 50 parts of fumed silica, 10 to 25 parts of a modified filler, 5 to 10 parts of a hydroxy silicone oil and 1 to 5 parts of a vulcanizing agent.

[0011] Furthermore, the silicone rubber matrix is ​​methylphenylvinyl silicone rubber.

[0012] Furthermore, the cross-linking agent is one of maleimide, N,N'-(4,4'-methylenediphenyl)bismaleimide, and 1-[3,5-bis(2,5-dioxo-1-pyrrolyl)phenyl]pyrrole-2,5-dione.

[0013] The preparation method of the modified filler comprises the following steps:

[0014] Select glass fiber as filler and add it to ethanol. After it is evenly dispersed, add 5-ethylene-2-hydroxybenzoic acid, heat to 60-80°C and stir for 2-6 hours. After stirring, filter it, wash the residue with ethanol three times, and dry it to obtain a modified filler.

[0015] Furthermore, the mass ratio of the glass fiber to ethanol is 1:2-5.

[0016] Furthermore, the added amount of the 5-ethylene-2-hydroxybenzoic acid is 10-20% of the mass of the glass fiber.

[0017] A preparation process of a glass fiber ceramic silicone sheet comprises the following steps:

[0018] The silicone rubber matrix, crosslinking agent, hydroxy silicone oil and fumed silica are mixed and kneaded, and then the modified filler is added and kneaded. After uniform mixing, the vulcanizing agent is added, and the product is vulcanized by flat-plate molding and extrusion. After secondary vulcanization by air drying, the product is die-cut, inspected and packaged.

[0019] Furthermore, the mixing temperature is 100-150°C.

[0020] Furthermore, the primary vulcanization temperature is 150-180° C., the vulcanization pressure is 10-16 MPa, and the time is 10-20 min.

[0021] Furthermore, the temperature of the secondary vulcanization is 180-200° C., and the time is 2-3 hours.

[0022] Furthermore, the vulcanizing agent is selected from one of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, bis-(2,4-dichlorobenzoyl) peroxide, bis(4-methylbenzoyl) peroxide, dibenzoyl peroxide, and tert-butyl perbenzoate.

[0023] Beneficial effects of the present invention:

[0024] 1. The present invention obtains the glass fiber ceramic silicone sheet by die-cutting after mixing the components, performing primary vulcanization and secondary vulcanization. The material is transformed from a flexible rubber state to a hard ceramic body under high temperature or open flame. On the one hand, it can play a role in blocking and isolating flames and temperature, isolating the protected material from the outside world. On the other hand, the heat insulation sheet has good strength and self-supporting properties, can withstand certain external impacts, and protects the material from being damaged by external forces as much as possible. Therefore, it is suitable for use in fields such as batteries that require high temperature stability.

[0025] 2. Compared with the prior art, the present invention utilizes inorganic fillers and multi-reactive functional group cross-linking agents to enhance the mechanical properties of the silicone rubber matrix from both chemical and physical levels, and at the same time utilizes modifiers to modify the filler surface to improve the interface compatibility between the inorganic filler and the silicone rubber matrix, thereby achieving an effective improvement in mechanical strength. DETAILED DESCRIPTION

[0026] Methylphenyl vinyl silicone rubber, phenyl content 40%, model: IOTA120, Anhui IOTA silicone oil.

[0027] 1-[3,5-bis(2,5-dioxo-1-pyrrolyl)phenyl]pyrrole-2,5-dione, CAS No.: 21217-67-4.

[0028] Fumed silica, 200 mesh.

[0029] Glass fiber, 300 mesh.

[0030] Example 1

[0031] A preparation process of a glass fiber ceramic silicone sheet comprises the following steps:

[0032] 1000g of methylphenyl vinyl silicone rubber, 10g of 1-[3,5-bis(2,5-dioxo-1-pyrrolyl)phenyl]pyrrole-2,5-dione, 60g of hydroxy silicone oil and 300g of fumed silica are mixed and kneaded, and then 150g of modified filler is added and kneaded at a mixing temperature of 120°C. After mixing evenly, 10g of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane is added, and the mixture is vulcanized by flat-plate molding and extrusion. The mixture is vulcanized at 160°C and 16MPa for 10min, and then secondary vulcanized by air drying at 180°C for 2h. The mixture is die-cut and packaged after inspection.

[0033] The preparation method of the modified filler comprises the following steps:

[0034] Glass fiber was selected as filler and added to ethanol. After uniform dispersion, 5-ethylene-2-hydroxybenzoic acid was added, and the mixture was heated to 70°C and stirred for 4 hours. After stirring, the mixture was filtered, and the residue was washed with ethanol for 3 times and dried to obtain a modified filler.

[0035] The mass ratio of the glass fiber to ethanol is 1:3.

[0036] The added amount of the 5-ethylene-2-hydroxybenzoic acid is 15% of the mass of the glass fiber.

[0037] Example 2

[0038] The same as Example 1, the only difference is that maleimide is used instead of 1-[3,5-bis(2,5-dioxo-1-pyrrolyl)phenyl]pyrrole-2,5-dione.

[0039] Example 3

[0040] The same as Example 1, the only difference is that N,N'-(4,4'-methylenediphenyl)bismaleimide is used instead of 1-[3,5-bis(2,5-dioxo-1-pyrrolyl)phenyl]pyrrole-2,5-dione.

[0041] Example 4

[0042] Same as Example 1, the only difference is that the modified filler is 100g.

[0043] Example 5

[0044] Same as Example 1, the only difference is that the modified filler is 200g.

[0045] Comparative Example 1

[0046] A preparation process of a glass fiber ceramic silicone sheet comprises the following steps:

[0047] 1000g of methylphenyl vinyl silicone rubber, 60g of hydroxy silicone oil and 300g of fumed silica are mixed and kneaded, and then 150g of modified filler is added and kneaded at a mixing temperature of 120°C. After mixing evenly, 10g of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane is added, and the mixture is vulcanized by flat-plate molding and extrusion. The mixture is vulcanized at 160°C and 16MPa for 10min, and then secondary vulcanized by air drying at 180°C for 2h. The mixture is die-cut, inspected and packaged.

[0048] The preparation method of the modified filler comprises the following steps:

[0049] Glass fiber was selected as filler and added to ethanol. After uniform dispersion, 5-ethylene-2-hydroxybenzoic acid was added, and the mixture was heated to 70°C and stirred for 4 hours. After stirring, the mixture was filtered, and the residue was washed with ethanol for 3 times and dried to obtain a modified filler.

[0050] The mass ratio of the glass fiber to ethanol is 1:3.

[0051] The added amount of the 5-ethylene-2-hydroxybenzoic acid is 15% of the mass of the glass fiber.

[0052] Comparative Example 2

[0053] A preparation process of a glass fiber ceramic silicone sheet comprises the following steps:

[0054] 1000g of methylphenyl vinyl silicone rubber, 10g of 1-[3,5-bis(2,5-dioxo-1-pyrrolyl)phenyl]pyrrole-2,5-dione, 60g of hydroxy silicone oil and 300g of fumed silica are mixed and kneaded, and then 150g of glass fiber is added as a filler and kneaded at a mixing temperature of 120°C. After mixing evenly, 10g of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane is added, and the mixture is vulcanized by flat-plate molding and extrusion, and vulcanized at 160°C and 16MPa for 10min. The mixture is then secondary vulcanized by air drying at 180°C for 2h, and then die-cut, inspected and packaged.

[0055] Comparative Example 3

[0056] A preparation process of a glass fiber ceramic silicone sheet comprises the following steps:

[0057] 1000g of methylphenyl vinyl silicone rubber, 10g of 1-[3,5-bis(2,5-dioxo-1-pyrrolyl)phenyl]pyrrole-2,5-dione, 60g of hydroxy silicone oil and 300g of fumed silica are mixed and kneaded, and then 150g of modified filler is added and kneaded at a mixing temperature of 120°C. After mixing evenly, 10g of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane is added, and the mixture is vulcanized by flat-plate molding and extrusion. The mixture is vulcanized at 160°C and 16MPa for 10min, and then secondary vulcanized by air drying at 180°C for 2h. The mixture is die-cut and packaged after inspection.

[0058] The preparation method of the modified filler comprises the following steps:

[0059] Glass fiber was selected as filler and added to ethanol. After uniform dispersion, oleic acid was added and the mixture was heated to 70°C and stirred for 4 hours. After stirring, the mixture was filtered and the residue was washed with ethanol for three times and dried to obtain a modified filler.

[0060] The mass ratio of the glass fiber to ethanol is 1:3.

[0061] The added amount of oleic acid is 15% of the mass of the glass fiber.

[0062] Test Example 1

[0063] The thermal insulation performance of the glass fiber ceramic silicone sheet was tested using a single digital display heating platform and an infrared thermal imager. The temperature of the heating platform was set to 200°C, and the sample was placed on the heating platform. The back temperature of the sample was tested every 30 seconds using an infrared thermal imager. The measured back temperature was approximated using the transition state plate method, and the thermal conductivity (λ) was calculated: λ = 0.1949L 2 Pt / (τ 1 / 2 ΔTV), L is the thickness of the sample; P is the thermal power of the heating platform; t is the heating time; τ 1 / 2 is the time required for the temperature of the back of the sample to rise by half; ΔT is the temperature difference of the back of the sample; V is the volume of the sample. See Table 1 for specific data.

[0064] Table 1 Thermal insulation performance test of glass fiber ceramic silicone sheet

[0065]

[0066]

[0067] It can be seen from the thermal insulation performance test that the glass fiber ceramic silicone sheets prepared by the present invention have a low thermal conductivity and good thermal insulation. This is because the glass fiber ceramic silicone sheet forms a hard ceramic structure on the surface at high temperature, which has the effect of flame retardancy and heat insulation. During the heating period, the silicone rubber composite material undergoes a series of phase changes. First, the surface silicone rubber matrix is ​​first oxidized and thermally decomposed to generate a large amount of SiO2. If the liquid phase has begun to be generated in the system at this time, SiO2 will adhere to the surface of the molten liquid phase and isolate the hot air from diffusing inward, otherwise a large amount of SiO2 will form a powdery detached material; as the temperature continues to rise, the added ceramic filler and the pyrolysis product undergo phase changes and crystal transformations to form a cross-linked network structure with a certain strength. The cross-linking agent participates in the addition reaction of the vinyl silicone rubber through multiple groups to increase the degree of cross-linking. On the other hand, the introduction of the cross-linking agent containing a rigid group can improve the thermal stability of the material. Therefore, the ceramic insulation sheet prepared in Example 1 has the best thermal insulation performance. The added filler has the characteristic of low thermal conductivity, so the thermal insulation performance can be improved after adding. However, the silicone rubber was not cross-linked in Control Example 1, and the glass fiber was not modified in Control Example 2, which affected the thermal stability of the composite material. In Control Example 3, oleic acid was used for modification. Although the compatibility was improved, the modifier in Example 1 can not only improve the compatibility but also improve the degree of cross-linking. Therefore, the interior of the material is tighter and the thermal stability is better.

[0068] Test Example 2

[0069] The mechanical properties of the glass fiber ceramic silicone sheet were tested. The tensile strength, elongation at break and tear strength were tested according to GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" and GB / T529-2008 "Determination of tear strength of vulcanized rubber or thermoplastic rubber", respectively. The test speed was 500mm / min. See Table 2 for specific data.

[0070] Table 2 Mechanical properties test of glass fiber ceramic silicone sheet

[0071]

[0072]

[0073] The application of glass fiber ceramic silicone sheet not only needs to meet the mechanical performance requirements of rubber body, but also needs to have certain mechanical performance requirements of ceramic body, that is, it has good rubber mechanical properties at room temperature, and the mechanical properties of ceramic body formed at high temperature are high and the ceramic body is dense. Glass fiber is added to the composite material to improve the thermal insulation performance and improve the mechanical properties. The cross-linking modification of silicone rubber is to improve the cross-linking degree of the material by chemical modification. By adding a cross-linking agent, the multifunctional reactive group and the vinyl in the silicone rubber undergo a cross-linking reaction and form a spatial network structure. The cross-linking agent in Example 1 not only has more cross-linking sites, but also can react with the silicone rubber matrix, and can further cross-link with the modified filler. In addition, the rigid groups possessed in the cross-linking agent structure can also improve thermal stability, so good fire retardancy can be guaranteed. By modifying the glass fiber, the surface energy is reduced, so the interface effect between it and the silicone rubber group is improved, so that the compatibility is better. However, the silicone rubber matrix is ​​not modified in the reference example 1, so the degree of the composite material is not as good as that of Example 1. In Comparative Example 2, the glass fiber was not modified, resulting in poor interfacial compatibility between the inorganic and organic phases, which greatly affected the mechanical properties of the material. The effect of reducing the surface energy by modification in Comparative Example 3 may not be as good as that in Example 1, so it may lead to poor compatibility and ultimately poor mechanical properties.

[0074] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A glass fiber ceramic silicone sheet, characterized in that: The invention comprises the following components in parts by weight: 80-150 parts of silicone rubber matrix, 1-2 parts of crosslinking agent, 20-50 parts of fumed silica, 10-25 parts of modified filler, 5-10 parts of hydroxy silicone oil and 1-5 parts of vulcanizing agent; The silicone rubber matrix is ​​methylphenyl vinyl silicone rubber; The cross-linking agent is one of maleimide, N,N'-(4,4'-methylenediphenyl)bismaleimide, and 1-[3,5-bis(2,5-dioxo-1-pyrrolyl)phenyl]pyrrole-2,5-dione; The preparation method of the modified filler comprises the following steps: Select glass fiber as filler and add it to ethanol. After it is evenly dispersed, add 5-ethylene-2-hydroxybenzoic acid, heat to 60-80°C and stir for 2-6 hours. After stirring, filter it, wash the residue with ethanol three times, and dry it to obtain a modified filler.

2. The glass fiber ceramic silicone sheet according to claim 1, characterized in that: The mass ratio of the glass fiber to ethanol is 1:2-5.

3. The glass fiber ceramic silicone sheet according to claim 1, characterized in that: The added amount of the 5-ethylene-2-hydroxybenzoic acid is 10-20% of the mass of the glass fiber.

4. A process for preparing a glass fiber ceramic silicone sheet according to any one of claims 1 to 3, characterized in that: The steps include: The silicone rubber matrix, crosslinking agent, hydroxy silicone oil and fumed silica are mixed and kneaded, and then the modified filler is added and kneaded. After uniform mixing, the vulcanizing agent is added, and the product is vulcanized by flat-plate molding and extrusion. After secondary vulcanization by air drying, the product is die-cut, inspected and packaged.

5. The process for preparing the glass fiber ceramic silicone sheet according to claim 4, characterized in that: The mixing temperature is 100-150°C.

6. The process for preparing the glass fiber ceramic silicone sheet according to claim 4, characterized in that: The temperature of the primary vulcanization is 150-180° C., the vulcanization pressure is 10-16 MPa, and the time is 10-20 min; the temperature of the secondary vulcanization is 180-200° C., and the time is 2-3 h.

7. The process for preparing the glass fiber ceramic silicone sheet according to claim 4, characterized in that: The vulcanizing agent is selected from one of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, bis-(2,4-dichlorobenzoyl) peroxide, bis(4-methylbenzoyl) peroxide, dibenzoyl peroxide, and tert-butyl perbenzoate.

Citation Information

Patent Citations

  • Preparation method of fire-preventing and fire-resisting silicon rubber capable of being ceramized

    CN104650597A

  • High temperature resistant ceramic silicone rubber, preparation method and application thereof

    CN110229526A

  • Fly ash-based ceramized silicone rubber composite material and preparation method thereof

    CN111635635A

  • Flexible ceramizable silicone rubber thermal insulation composite material and preparation method thereof

    CN111761895A